The needs of older persons undergoing heart surgery: unveiling a nursing intervention through focus groups. (14th October 2021) - Nicola Rodrigues, S; Rafael Henriques, H; Henriques, M A
Abstract: Background: The progressive ageing of the population, the prevalence of chronic diseases, such as cardiovascular diseases and heart disease with surgical indication, have a significant expression, either with a curative objective or to increase quality of life. Waiting for surgery is often a period of anxiety and fear. Preoperative waiting time can be used to better prepare these patients for surgery. Purpose: The purpose of this research was to identify the needs of older people waiting for heart surgery. Methods: A qualitative exploratory approach was used to gain an understanding of the participants' perception of what are the needs of older persons waiting for heart surgery. Focus Groups were used to collect information. Three interviews were conducted with: a group of nurses with experience in cardiothoracic care, individuals submitted to heart surgery (≥65 years) and individuals waiting for heart surgery (≥65 years); enrolling up to 17 participants from October 2019 to January 2020. Qualitative data analysis was conducted using the interactive model, at first similar data chunks were categorized by codes, allowing further analysis of data. Condensing data enabled us to retrieve the most significant material, further condensing it into smaller number of categories. The MaxQDA software, and EQUATOR COREQ guidelines were followed. Results: Three categories emerged: (i) Information focused on facilitating health promotion and self-care, information regarding the hospital stay and granting access to information; (ii) Emotional support described patient's feelings towards the upcoming surgery and the need to keep them calm, involving their families and caregivers; (iii) Access to care, patients should be kept involved and engaged in managing self-care. Conclusion: A preoperative intervention is necessary to support older persons waiting for heart surgery and the education provided should be focused on patients' needs. Caring for individuals awaiting heart surgery may be challenging due to the barriers imposed by physical distance and emotional distress. The identified needs of individuals awaiting heart surgery allow health professionals to deepen their knowledge regarding the patient's care. FUNDunding Acknowledgement: Type of funding sources: None.